BE AWARE OF WATER ZOMBIES: AN ECOCRITICAL STUDY ON SHUSTERMANS’ DRY - Sri Sartini; Endahati, Nafisah (Universitas Negeri Yogyakarta, 2023)
Natural damage, disaster, and catastrophe can happen due to human mistreatment toward the environment. Thus, there is an urgency to treat the environment better and to sustain the comfortable living of human life. Environmental issues in recent literary works are still tightly engaged due to people's high concern and attention toward the environment’s condition. The condition of the environment has been illustrated in a novel entitled Dry written by Neal and Jarrod Shusterman (2018). Through the ecocriticism literary perspective, this study sought to reveal the conditions of nature as the impact of human mistreatment in the aspect of six concepts brought by Greg Garrard (2004). Using his theory, this study explored the environmental damage and its implication as the result of human exploration of the environment from the aspect of pollution, wilderness, apocalypse, dwelling, animals, and the earth. This study employed content analysis to seek the intended objective. The findings declared that Dry successfully illustrated the existing environmental problems. The human-nature relation from the six concepts was described and exemplified very tightly that it is expected to wake the readers up to pay more concern and care toward the environment. At last, this study implied the need to analyze the human-nature relation through the specific concept of Garrard’s or other kinds of theory to sustain the environment with the ecocriticism perspective.